2022
DOI: 10.2147/ijgm.s354641
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Analysis of Potential Critical Gene in Acute Myocardial Infarction Based on a miRNA-mRNA Regulatory Network

Abstract: Background MicroRNAs (miRNAs) have been shown to be involved in the initiation, progression, and prevention of acute myocardial infarction (AMI), but the underlying mechanism remains unclear. Objective Through the GEO database, bioinformatics methods were used to explore the miRNA-mRNA regulatory relationship pairs associated with AMI and to elucidate the underlying mechanism. Methods Using the R software Limma package, differential expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…SFXN4 knockout in zebrafish caused mitochondrial respiratory defect and resulted in macrocytic anemia 23 . Furthermore, mutation in SFXN4 is correlated with prenatal onset of mitochondrial diseases, and presented with macrocytic anemia and optic nerve hypoplasia 43 , 44 . Recent studies revealed that SFXN1 and SFXN4 regulate mitochondrial respiratory chain through different mechanisms, SFXN1 was reported to the maintain the integrity of mitochondrial complex Ⅲ 14 , while SFXN4 coordinates the assembly of complex Ⅰ by interacting with MCIA complex, integrating mtDNA-encoded ND6 and promoting ND2-module maturation 45 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SFXN4 knockout in zebrafish caused mitochondrial respiratory defect and resulted in macrocytic anemia 23 . Furthermore, mutation in SFXN4 is correlated with prenatal onset of mitochondrial diseases, and presented with macrocytic anemia and optic nerve hypoplasia 43 , 44 . Recent studies revealed that SFXN1 and SFXN4 regulate mitochondrial respiratory chain through different mechanisms, SFXN1 was reported to the maintain the integrity of mitochondrial complex Ⅲ 14 , while SFXN4 coordinates the assembly of complex Ⅰ by interacting with MCIA complex, integrating mtDNA-encoded ND6 and promoting ND2-module maturation 45 .…”
Section: Discussionmentioning
confidence: 99%
“…By GWAS meta-analysis, SFXN4 SNP (rs150807690) was found to be implicated in stroke, suggesting SFXN4 was a potential ischemic stroke loci11 48 . Based on bioinformatics analysis, it was found that SFXN4 expression was upregulated during acute myocardial infarction 44 . Recently, Dang et al found that SFXN4 was upregulated in lung adenocarcinoma, and it had significant correlation with immune infiltration 49 .…”
Section: Discussionmentioning
confidence: 99%